Manajemen Edukasi Pendidikan Agama Oleh Pemerintah Gampong Cucum Melalui Kegiatan Festival Anak Sholeh Sebagai Upaya Peningkatkan Pengetahuan Dan Kreativitas Anak Dalam Rangka Memperingati Maulid Nabi - Ira Octavia; Muslem Muslem (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Gampong administration is carried out by people who have been trusted by the community both to lead and take care of all the interests of the gampong. In addition to being responsible for the administration of the gampong, the gampong government is assisted by gampong officials who are also tasked with organizing religious, customary, cultural activities and driving educational and economic programs for the gampong. Gampong community activities, especially in Aceh, cannot be separated from the religious and cultural values ​​in them, one of which is the celebration of the Prophet's Birthday. In the perspective of the Cucum village community, the level of success of the event is assessed from the programs and activities included in the celebration of the Prophet's birthday. The programs and activities that are filled are expected to be able to reflect religious, cultural and customary values ​​in the region, as well as being able to improve the level of education and the village economy. For this reason, the Gampong Cucum government held a competition entitled